Developing JF standard-based digital grammar resources for intermediate Japanese language education: Research and best practices - Sarjani, Andi Irma; Iskandar, Ifan; Attas , Siti Gomo (BAHASTRA, 2025)
Japanese language education in Indonesia faces critical challenges in intermediate grammar instruction regarding alignment with international standards, active learning integration, and digital resource availability. This study evaluates existing intermediate Japanese grammar materials against JF Standard requirements and develops a practical framework for creating digital resources. Employing design-based research methodology, this study analyzed materials from 10 Indonesian universities, conducted needs analysis surveys with 105 intermediate learners, developed the "Nihongo with Irma Sensei" prototype, and validated materials through expert evaluation and field testing. Findings reveal substantial gaps: 0% inclusion of JF Standard components (Can-do statements, communicative competence frameworks, learner portfolios), 15% active learning integration, and 8% digital availability. Field testing showed 96% participant interest in digital materials and 96.1% acknowledged enhanced comprehension. The study identifies five best practices: contextualized presentation through multimedia, interactive exercises with immediate feedback, multimodal approaches, strict JF Standard alignment, and user-centered design. This research demonstrates the feasibility and effectiveness of JF Standard-aligned digital materials leveraging multimedia technologies to facilitate contextualized and communicative language learning.